2013
DOI: 10.1097/pec.0b013e3182854465
|View full text |Cite
|
Sign up to set email alerts
|

Mass Screening for Fever in Children

Abstract: Compared with traditional thermometry, FLIR and OptoTherm were reasonably accurate in detecting fever in children and better predictors of fever than parental report. These findings suggest that ITDSs could be a useful noninvasive screening tool for fever in the pediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 36 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…In a study by Allagaert et al (12) who compared the infrared skin temperature measurement with rectal measurement in order to reflect core temperature, it was reported that temperature measurements by NCITs had been underperformed when compared with rectal measurement. Likewise, underperformance of our infrared skin scan results to detect fever also confirms previous studies (13,14) . There are very few studies about the effectiveness and reliability of NCITs.…”
Section: Discussionsupporting
confidence: 75%
“…In a study by Allagaert et al (12) who compared the infrared skin temperature measurement with rectal measurement in order to reflect core temperature, it was reported that temperature measurements by NCITs had been underperformed when compared with rectal measurement. Likewise, underperformance of our infrared skin scan results to detect fever also confirms previous studies (13,14) . There are very few studies about the effectiveness and reliability of NCITs.…”
Section: Discussionsupporting
confidence: 75%
“…Sensitivity, specificity, positive predictive value, and negative predictive value for rectal fever (38°C) were 80%, 97%, 91%, and 94% for tympanic and 64%, 96%, 84%, and 89% for an infrared method 6 . Finally, Selent et al 13 compared 3 different infrared thermal skin detection systems (OptoTherm Thermoscreen, Sewickley, PA; FLIR ThermoVision 360, Boston, MA; and Thermofocus), and documented that sensitivity (compared with 38°C rectal) was between 77% and 84%; specificity was between 79% and 86%.…”
Section: Discussionmentioning
confidence: 90%
“…Only a few studies have compared IFR thermometers with axillary devices in children, and the results have been inconsistent. [ 9 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a moderate correlation between axillary and IFR temperature ( r =0.66, P = .001) was observed in another study. [ 9 ] Chiappini et al [ 10 ] found a strong correlation between IFR measurements and axillary temperatures in 251 children ( r = 0.84). However; a mercury-in-glass thermometer was used for axillary measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation